Lung function in asbestos-exposed workers, a systematic review and meta-analysis - Wilken Dennis; Garrido Marcial; Manuwald Ulf; Baur Xaver (Journal of Occupational Medicine and Toxicology, 2011)
Abstract Background A continuing controversy exists about whether, asbestos exposure is associated with significant lung function impairments when major radiological abnormalities are lacking. We conducted a systematic review and meta-analysis in order to assess whether asbestos exposure is related to impairment of lung function parameters independently of the radiological findings. Methods MEDLINE was searched from its inception up to April 2010. We included studies that assessed lung function parameters in asbestos exposed workers and stratified subjects according to radiological findings. Estimates of VC, FEV1 and FEV1/VC with their dispersion measures were extracted and pooled. Results Our meta-analysis with data from 9,921 workers exposed to asbestos demonstrates a statistically significant reduction in VC, FEV1 and FEV1/VC, even in those workers without radiological changes. Less severe lung function impairments are detected if the diagnoses are based on (high resolution) computed tomography rather than the less sensitive X-ray images. The degree of lung function impairment was partly related to the proportion of smokers included in the studies. Conclusions Asbestos exposure is related to restrictive and obstructive lung function impairment. Even in the absence of radiological evidence of parenchymal or pleural diseases there is a trend for functional impairment.